Validity Of LKPD Based Project Based Learning On Global Warming Material For Phase E Students At SMAN 1 Banuhampu - Fio Adella Illahi; Darvina, Yenni; Desnita, Desnita; Gusnedi, Gusnedi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
The implementation of an independent curriculum requires adaptation in its application, especially in the readiness of project-based teaching materials. However, the LKPD in SMA N 1 Banuhampu is still not in accordance with the standards of teaching materials needed and expected in learning using an independent curriculum.The research method used in this research is R&D with a 4D research model consisting of four research steps, namely define, design, development, and desseminate. The data collection technique from this study uses a validation instrument that will be assessed by three validators. Based on the results, it was concluded that the results of making project-based learning LKPD on global warming material have obtained valid with a validity index of presentation aspects of 0.872, graphic aspects 1, feasibility aspects of content 0.914 and linguistic aspects of 0.889. Thus, project-based learning LKPD products phase E students can be used in the learning process.